Rowing in the same direction: Role understanding and co-leadership between two employer lines in the Church of Norway (Nordic Journal of Practical Theology, 2025)
The article examines collective leadership where individuals share leadership functions. Considering perspectives on plural, shared leadership, and leader role theory, it explores co-leadership in the Church of Norway. The church is organized into two employer lines. The dioceses manage the clergy on behalf of the national legal entity, while the local parochial church councils manage other church employees. The organization of two entities in the same location requires good collaboration between the leaders to create one well-functioning local church. The article is based on an interview study among local church leaders, investigating how co-leadership becomes a tool to address challenges and opportunities within the dual organizing. The research question is: How do senior pastors and general managers understand each other’s leader roles, and how can their shared role space develop co-leadership within the Church of Norway’s dual employer organizing? The article provides a definition of co-leadership as well as a model showing how the duos emphasize three dimensions in co-leadership: building role understanding, ensuring communication infrastructures, and developing the organization.
Keywords: Co-leadership; Shared leadership; Role space; Pastor; General manager; Church